2004
DOI: 10.1097/01.ta.0000123698.76058.85
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shock and Fluid Resuscitation on the Morphology and Apoptosis of Bone Marrow: An Experimental Study

Abstract: There was an increase in bone marrow apoptosis after hemorrhagic shock. The type of resuscitation scheme used did influence bone marrow morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…57 In another study, we have shown that hypertonic saline may exert its long-term benefits after hemorrhagic shock by modulating bone marrow apoptosis. 58 , a mechanism that has been linked to sepsis and multiple organ dysfunctions. 59 Hypertonic saline resuscitation may also influence the transcriptional, functional and protein expression of genes related to Matrix metalloproteinases (MMPs) and their specific physiological inhibitors, tissue inhibitors of metalloproteinases (TIMPs), which are thought to play an essential role in tissue repair, cell death and morphogenesis.…”
Section: Immune and Inflammatory Effects Of Hs/ Hsdmentioning
confidence: 99%
“…57 In another study, we have shown that hypertonic saline may exert its long-term benefits after hemorrhagic shock by modulating bone marrow apoptosis. 58 , a mechanism that has been linked to sepsis and multiple organ dysfunctions. 59 Hypertonic saline resuscitation may also influence the transcriptional, functional and protein expression of genes related to Matrix metalloproteinases (MMPs) and their specific physiological inhibitors, tissue inhibitors of metalloproteinases (TIMPs), which are thought to play an essential role in tissue repair, cell death and morphogenesis.…”
Section: Immune and Inflammatory Effects Of Hs/ Hsdmentioning
confidence: 99%
“…Immediate plasma volume expansion due to intracellular fluid mobilization, particularly from erythrocytes and endothelial cells, promotes systemic hemodynamic benefits and microcirculatory blood flow improvement [ 12 , 13 , 15 - 18 ]. Moreover, in comparison with lactated Ringer's solution (LR) resuscitation, we demonstrated that HS resuscitation reduces bacterial translocation and lung injury after hemorrhage [ 19 ], and avoids morphological alterations in bone marrow seen after hemorrhagic shock [ 20 ]. It has also been shown that hypertonic saline reduces neutrophil-endothelium interactions and vascular leakage [ 21 ], and attenuates neutrophils' cytotoxic response post-injury [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…61,63 The mechanism evolved in the action of hypertonic solution in sepsis have been related to hemodynamic effects 39,[44][45][46][47]52,64,65 and immunomodulatory reducing release of proinflammatory cytokines, expression of L-selectin as well as the oxidative burst in the neutrophil. 43,45,[66][67][68][69][70][71][72][73] Other kind of effects have been reported, Parreira et al 41 showed that hypertonic solution changes brown fat tissue protecting from hemorrhagic shock and it has been also demonstrated in sepsis and MODS. 74…”
Section: Experimental Studies With Hypertonic Saline Solution (Hss)mentioning
confidence: 99%